Dynamics of COVID-19 Incorporating Preventive Measures and Treatment - Arierhie, Eirene O; Akponana, Eloho B; Egbune, Ngozika J; Okedoye, Akindele Michael (JURNAL DIFERENSIAL, 2024)
The surge of Coronavirus disease (COVID-19) was felt all over the world greatly after it was declared a pandemic in the year 2020. After 3 years in 2023, the disease passed the pandemic phaseand entered an endemic phase. But that didn’t reduce the global threat of the disease as the disease continues to still claim lives daily. In this work, we examined the dynamics of the coronavirusdisease from a mathematical view using a deterministic SEIAISQVRIP LP model. This consists ofinvestigating the disease-free and endemic equilibria, basic reproduction number and stability. Thelocal stability of the disease-free equilibrium was determined by solving the Jacobian matrix of thesystem of the system of differential equations while the basic reproduction number was calculatedusing the next generation matrix method. Numerical simulations to determine the active factor(s) inthe transmission, preventive and possible elimination of the disease were carried out using a computational software called Maple. It was revealed that over time when all modalities are out into place the rate of recovery increases and as the rate of the pathogen virus death increases, the pathogen virus gradually fades from the environment.